Diatoms and bacteria diversity: study of their relationships in the Southern Adriatic Sea - CAROPPO, C.; STABILI, L.; CAVALLO, R.A. (Mediterranean Marine Science, 2003)
In the Southern Adriatic Sea (Italian coasts) bacterial and diatom diversity was studied over an annual cycle and the relationships between these two microbial components were analyzed. As regards the culturable heterotrophic bacteria, Aeromonas was the predominant genus among the Gram-negative bacteria. The presence of Enterobacteriaceae, Cytophaga, Pseudomonas, Acinetobacterand Photobacteriumwas also remarkable. Flexibacter, Moraxella, Chromobacterium, Flavobacteriumand Vibriowere present at less than 5%. Of the 92 diatom species determined, 16 were the most abundant representing the 96% of this phytoplankton group. The results obtained demonstrated that several bacterial genera were significantly related to the most abundant and representative diatoms ( Chaetocerosspp., Pseudo-nitzschia pseudodelicatissimaand Rhizosoleniaspp.).